Macromol. Rapid Commun. 15/2014. Issue 15 (August 2014) - Basak, Dipankar; Kumar, Rajan; Ghosh, Suhrit
<x xml:space="preserve">Abstract</x> Back Cover: An efficient polycondensation route for telechelic poly(disulfide)s is developed from two monomers—2, 2′‐dithiodipyridine and 1, 6‐hexanedithiol—using stoichiometric imbalance between them. Selective thiol‐disulfide exchange of the two terminal pyridyl disulfide groups with functional thiol produces functionalized poly(disulfide)s that can be used as a macro‐initiator to initiate ROP of lactide generating a triblock copolymer with degradable middle block. Further details can be found in the article by D. Basak, R. Kumar, and S. Ghosh* on page 1340. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>